FORMULASI DAN UJI STABILITAS FISIK FACIAL WASH GEL EKSTRAK BUAH LABU KUNING (Cucurbita moschata D.) DENGAN VARIASI KONSENTRASI CARBOPOL 940 - Diyana Wulandari; Gigih Kenanga Sari; Maulita Saraswati (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
Yellow pumpkin fruit (Cucurbita moschata D.) is one of the plants that have antioxidant activity. This study aims to determine the characteristics and physical stability of facial wash gel preparation pumpkin extract (Cucurbita moschata D.) with variations in the concentration of carbopol 940. Facial wash gel made 3 formulas with different concentrations of carbopol 940, FI 1%, FII 1.5%, and FIII 2%. The physical stability test of facial wash gel preparation is carried out by room temperature storage and cycling test with parameters including organoleptic test, homogeneity test, pH test, dispersion test, foam stability test, and viscosity test. The results showed that formula I with carbopol 940 concentration of 1% resulted in the best stability properties of the gel preparation. The statistical data of One-Way ANOVA test showed a significant difference between pH, dispersibility, foam stability, and viscosity of facial wash gel preparation against the difference in carbopol 940 concentration with significance value (p<0.05).